Mediation effects of need for cognitive closure on the relationship between relational mobility and subjective well-being - Ng, Dorothy Xin En (2017)
Subjective well-being has been widely studied in many domains of research, such as psychology, philosophy, or even economics. Top-down and bottom-up factors have previous been studied to impact subjective-wellbeing. This study seeks to find out how the top-down construct of relational mobility and the bottom-up construct of Need for Cognitive Closure (NFC) interact to affect the experience of subjective well-being. It is hypothesized that there is a direct relationship between relational mobility and subjective well-being. This study also aims to test whether NFC is a mediator of this hypothesized relationship. Results failed to detect a significant relationship between relational mobility and subjective well-being, though there was a slight positive relationship between the variables. NFC also was not a significant mediator between relational mobility and subjective well-being. While there was no empirical support for the hypotheses, this study contributes to the current literature pertaining to subjective well-being.